2006
DOI: 10.1590/s0102-311x2006000800002
|View full text |Cite
|
Sign up to set email alerts
|

Capital social e a agenda de pesquisa em epidemiologia

Abstract: IntroduçãoNos últimos anos, o conceito de "capital social" tem sido utilizado na literatura internacional em uma vasta gama de disciplinas entre as quais: sociologia, antropologia, educação, economia, ciências políticas, criminologia e saúde pública. Trata-se de um conceito desafiador, pois incorpora o freqüentemente negligenciado "social" com o onipotente "capital". Capital social enfatiza o fato de que formas e relações não-monetárias podem ser importantes fontes de poder e influência 1 .Sua proeminência rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
22

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 96 publications
1
11
0
22
Order By: Relevance
“…Several studies have shown associations between adolescent substance use and affi liation with peer substance use and positive attitudes and expectations, for, and acceptance of, substance use (Simões, 2007). The relationships between substance use and family, classmates, and teachers appeared to be work mainly through their association with intervening factors, suggesting the importance of social relationships (Huver et al, 2007;Pattussi, Moyses, Junges, & Sheiham, 2006). Consistent with other fi ndings (Greeff & le Roux, 1999;Weitoft et al, 2003), the relationships between family and classmates with substance use were mainly through their negative associations with psychological symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have shown associations between adolescent substance use and affi liation with peer substance use and positive attitudes and expectations, for, and acceptance of, substance use (Simões, 2007). The relationships between substance use and family, classmates, and teachers appeared to be work mainly through their association with intervening factors, suggesting the importance of social relationships (Huver et al, 2007;Pattussi, Moyses, Junges, & Sheiham, 2006). Consistent with other fi ndings (Greeff & le Roux, 1999;Weitoft et al, 2003), the relationships between family and classmates with substance use were mainly through their negative associations with psychological symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…21 A historical synthesis of the concept, its capacity to infer health differentials and measurement tools were recently presented to the professional fi eld of public health in Brazil. 15,18 Exemplifying the application of this concept, Pattussi et al 14 studied dental injuries among adolescents residing in two satellite cities of Brasilia. An extensive questionnaire and a complex statistical procedure were used to characterize social capital as an attribute of residential areas.…”
Section: Social Capitalmentioning
confidence: 99%
“…En relación con la confianza generalizada, Colombia se encuentra entre los países que presentan menores niveles; sin embargo, esta relación ya se ha descrito en la literatura internacional especializada y se sabe que su efecto sobre la esperanza de vida al nacer no es muy acentuado (36,44). Al revisar la percepción de corrupción, el país se ubica en las posiciones intermedias, siendo su efecto sobre la esperanza de vida al nacer un tanto mayor que el de la confianza generalizada.…”
Section: Macrodeterminanteunclassified